1989
DOI: 10.3109/00365528909093067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral S-Adenosyl-l-Methionine on Hepatic Glutathione in Patients with Liver Disease

Abstract: S-Adenosyl-L-methionine (SAMe) is a physiologic precursor of thiols and sulfurated compounds, which are known to be decreased in patients with liver disease. The effect of its administration on the hepatic glutathione content of liver patients was investigated. Four groups of subjects were selected: a) 9 patients with alcoholic liver disease treated with SAMe (1.2 g/day orally for 6 months); b) 7 patients with non-alcoholic liver disease treated as above; c) 8 placebo-treated patients with alcoholic liver dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
2
10

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(93 citation statements)
references
References 24 publications
3
78
2
10
Order By: Relevance
“…[21][22][23][24] Oral AdoMet treatment has therefore been used in animal models and in patients to restore GSH content in the liver with the aim to treat liver diseases. [25][26][27] We were interested in AdoMet not because of its role in GSH biosynthesis, 28,29 but because PRMT1 uses AdoMet as the methyl group donor for STAT1 methylation (Fig. 1D).…”
Section: Expression Of Pp2ac In Human Liver Biopsiesmentioning
confidence: 99%
“…[21][22][23][24] Oral AdoMet treatment has therefore been used in animal models and in patients to restore GSH content in the liver with the aim to treat liver diseases. [25][26][27] We were interested in AdoMet not because of its role in GSH biosynthesis, 28,29 but because PRMT1 uses AdoMet as the methyl group donor for STAT1 methylation (Fig. 1D).…”
Section: Expression Of Pp2ac In Human Liver Biopsiesmentioning
confidence: 99%
“…1,2 Administration of SAM in patients and animals with alcoholic liver disease restored hepatic GSH levels. 20,21 A third factor that can contribute to depletion of liver GSH level is increased GSH efflux, mediated by endotoxin. 43 Increased endotoxin levels occur in animal models of alcoholic liver disease, 44 and treatment with antibiotics attenuated liver injury.…”
Section: Figmentioning
confidence: 99%
“…Patients with alcoholic liver disease have lower hepatic GSH levels, which appears to be independent of nutritional status and probably reflects increased oxidative stress. [18][19][20] Baboons fed ethanol also chronically exhibit a lower hepatic GSH level. 21 In 1 study, rats fed ethanol in a Lieber-DeCarli diet for 16 days had markedly reduced hepatic GSH levels, 22 but another study that fed rats the same diet for 4 weeks showed little change.…”
mentioning
confidence: 99%
“…13 Surgery and taurine. 2,4 in the sham-operated group was performed with the same procedure except that the bile duct was not ligated.…”
Section: Tbars Sam Had the Dose-dependent Effects Of Inhibitingmentioning
confidence: 99%